1997
DOI: 10.1111/j.1600-065x.1997.tb00996.x
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine stew and innate resistance to L. monocytogenes

Abstract: The Listeria monocytogenes (L. monocytogenes) infection model has been a useful system to evaluate the cellular interactions leading to host immunity. The initiation of the innate immune response in naive animals and subsequent progression to acquired immunity represent an integrated system with numerous layers of complexity. Coincident with experimental infection is the induction of cytokines. Cytokines, which are soluble mediators of cell growth, maintenance and function, from a network of pleiotropic stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
6

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 62 publications
3
41
0
6
Order By: Relevance
“…While reconstitution with IFN-+ -/-NK cells was unable to increase resistance of + c -/-(y) -Rag-2 -/-mice to L. monocytogenes infection, adoptive transfer of IFN-+ R -/-NK cells increased resistance to infection. These results together with previous results using beige mice or perforin-knockout mice [37,45] establish that cytotoxic activity of NK cell has little role, if any, in the innate resistance to foreign pathogens in vivo.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…While reconstitution with IFN-+ -/-NK cells was unable to increase resistance of + c -/-(y) -Rag-2 -/-mice to L. monocytogenes infection, adoptive transfer of IFN-+ R -/-NK cells increased resistance to infection. These results together with previous results using beige mice or perforin-knockout mice [37,45] establish that cytotoxic activity of NK cell has little role, if any, in the innate resistance to foreign pathogens in vivo.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have suggested that NK cells contribute to controlling early infection with intracellular pathogen [32,36,37]. To assess the role of NK cells, Rag-2 -/- (Fig.…”
Section: Contribution Of Nk Cells In Protection Against L Monocytogementioning
confidence: 99%
“…Indeed, protection against primary LM infection in immunocompetent hosts is mediated mainly by the innate immune system. 29 It is known that innate immune cells upregulate expression of cIAPs during differentiation and activation, 4,20,30 however, their function during an immune Our results show that the degradation of cIAPs through application of SMAC mimetic (SM) results in macrophage cell death. This result appears to contradict a recent report showing that human monocytes are susceptible to SMinduced cell death whereas macrophages are resistant.…”
Section: Discussionmentioning
confidence: 66%
“…We infected mice with the intracellular bacterium, Listeria monocytogenes (LM), as it causes illness in immune compromised hosts, with the innate immune system having a key role in control of infection. 29 At 3 days post infection we found that SM-treated mice showed an approximately 10-fold (Figure 8a). This correlated to decreased numbers and increased cell death of macrophages in SM-treated mice, while T-cell pools were largely unaffected (Figures 8b and c).…”
Section: Resultsmentioning
confidence: 96%
“…Infected cells can express a variety of cytokines, including ␤-IFN, which alert the host immune system to the presence of an infectious agent. Macrophages play an especially important role in promoting the differentiation of immune effector cells; in general, the response of the first infected cells in a host organism shapes subsequent innate and adaptive immunity to L. monocytogenes (11).…”
mentioning
confidence: 99%